Assessing the Utility of Organoid Intelligence: Scientific and Ethical Perspectives - Michael W. Nestor; Richard L. Wilson (Organoids)
The development of brain organoids from human-induced pluripotent stem cells (iPSCs) has expanded research into neurodevelopment, disease modeling, and drug testing. More recently, the concept of organoid intelligence (OI) has emerged, proposing that these constructs could evolve to support learning, memory, or even sentience. While this perspective has driven enthusiasm in the field of organoid research and suggested new applications in fields such as neuromorphic computing, it also introduces significant scientific and conceptual concerns. Current brain organoids lack the anatomical complexity, network organization, and sensorimotor integration necessary for intelligence or sentience. Despite this, claims surrounding OI often rely on oversimplified interpretations of neural activity, fueled by neurorealist and reification biases that misattribute neurophysiological properties to biologically limited systems. Beyond scientific limitations, the framing of OI risks imposing ethical and regulatory challenges based on speculative concerns rather than empirical evidence. The assumption that organoids might possess sentience, or could develop it over time, could lead to unnecessary restrictions on legitimate research while misrepresenting their actual capabilities. Additionally, comparing biological systems to silicon-based computing overlooks fundamental differences in scalability, efficiency, and predictability, raising questions about whether organoids can meaningfully contribute to computational advancements. The field must recognize the limitations of these models rather than prematurely defining OI as a distinct research domain. A more cautious, evidence-driven approach is necessary to ensure that brain organoids remain valuable tools for neuroscience without overstating their potential. To maintain scientific credibility and public trust, it is essential to separate speculative narratives from grounded research, thus allowing for continued progress in organoid studies without reinforcing misconceptions about intelligence or sentience.